Perencanaan Strategi Pengembangan Mutu di Lembaga Pendidikan Islam - Sunardi, Sunardi; Zaenuri, Zaenuri; Hajras, Multazam (Jurnal Manajemen dan Budaya, 2025)
Quality education is a dream for education managers. To achieve these goals and expectations, Islamic educational institutions must be able to implement and apply various strategies in managing educational institutions. This strategy is formulated based on proper planning, good implementation, and continuous evaluation. This research uses a qualitative-analytical approach. Data collection uses observation, interviews and documentation. Data analysis uses the Miles and Hubermen interactive analysis model which includes four components, namely data collection, reduction, presentation and drawing conclusions. Checking the validity of the data uses credibility, transferability, dependability and confirmability. The results of this research show that The strategic planning carried out by the Darul Kamal NW Kembang Kerang Islamic Boarding School involved various parties (stakeholders) from academic circles, religious leaders, community leaders and other figures through the formulation of vision and mission, formulation of goals and targets education, as well as determining strategies.